Optimization Mechanism of Resource Transfer Processes Between Company Codes Using “Stock in Transit” - Konrad BANDURSKI; Piotr JAKUBOWSKI; Rafał JANKOWIAK; Grzegorz BLIZNIUK (Communications of International Proceedings, 2022)
The article presents a description and application of the Stock in Transit mechanism in the process of transferring resources between company codes. The mechanism in question is a functionality of SAP ERP technology for complex enterprise management, provided by the pioneering SAP company, currently the global market leader in ERP software. The work presents the developed solution to the problem of discontinuity of resource recording in the system due to periodic occurrence of the phenomenon of "disappearance of resources". The above solution using the Stock in Transit mechanism was then compared against other solutions.
Keywords: Stock in Transit; Enterprise Resource Planning; SAP; ERP